Safety and clinical activity of target-preserving anti-CTLA-4 antibody ONC-392 as monotherapy in NSCLC patients who progressed on PD(L)1-targeted immunotherapy - Carbone, David Paul; McKean, Meredith; Balaraman, Rama; Shah, Satish; Arrowsmith, Edward; Peguero, Julio Antonio; Joshi, Rohit; He, Aiwu Ruth; Milillo, Adriana; Hamm, John Turner; Goldstein, Mark Gregory; Li, Zihai; et al. (Journal of clinical oncology, 2023)
9024Background: PD-1 or PD-L1 inhibitors have transformed clinical care of NSCLC patients. However, many patients may develop primary or secondary resistant to PD-(L)1 inhibitors. The marketed anti-CTLA-4 mAbs are ineffective as monotherapy for NSCLC. ONC-392 is a novel target-preserving anti-CTLA-4 antibodies that confers immunotherapeutic effect by selective depletion of regulatory T cells (Treg) in the tumor microenvironment. Preclinical studies show that ONC-392 is more effective and less toxic for immunotherapy than other clinically used anti-CTLA-4 antibodies. In first-in-human study in patients with advanced solid cancer, the recommended Phase 2 dose (RP2D) for ONC-392 monotherapy was established as 10 mg/kg. In this study, we tested safety and clinical activities of ONC-392 in NSCLC patients who progressed on PD(L)1-targeted therapy. Methods: Anti-PD-(L)1 resistant NSCLC patients were enrolled as parts of PRESERVE-001 studies (NCT04140526) expansion cohort Part C Arm I and treated with 2 cycles of 10 mg/kg, followed by 6 mg/kg, q3w, ONC-392 by IV infusion. Safety was evaluated based on treatment emergent and treatment-related adverse events, while efficacy was evaluated by investigators using RECIST1.1 criteria. Results: As of December 18, 2022, 33 NSCLC patients have received at least one dose of ONC-392 at 10 mg/kg. The median age is 66 yrs (range 43 - 89 yr), 61% male. 61% were non-squamous cell carcinoma and 39% were squamous cell carcinoma. 27% are ECOG score 0 and 73% were ECOG score 1. The median prior treatment was 2 cycles (range 1 to 4). The average ONC-392 treatment period was 3.5 cycles (range 1 to 13 cycles). Overall, the patients with TRAE in grade 3 or above is 33% (11/33), including diarrhea/colitis (3, 9%), AST/ALT increase or hepatitis (3, 9%), muscular weakness (2, 6%), nephritis (1, 3%), adrenal insufficiency (1, 3%). Due to pace of enrollment, efficacy data are available in 22 patients. 6 of 22 evaluable patients have partial response and 12 patients have stable disease per RECIST 1.1, resulting in a response rate of 27% and disease control rate of 82% among evaluable patients. The median follow-up period for all patients is 5.8 months and 8.6 months for 20 alive patients (range 2.9 to 14.1 months). The estimated 6- and 12-month overall survival (OS) rates were 65% and 55%. Median OS has not reached. Conclusions: Overall, ONC-392 monotherapy with 10 mg/kg is safe and tolerable. Onc-392 monotherapy has showed encouraging anti-tumor activity in IO-resistant NSCLC when compared with historical data. Based on these encouraging data, we have initiated a Phase 3 study testing ONC-392 monotherapy among NSCLC who progressed on PD(L)1-targeting immunotherapy (NCT05671510). Clinical trial information: NCT04140526.